أيديولوجية فرحات عباس في التحري عن كينونة الجزائر أمة ووطن بتحليل دوره في انتخابات 1946م- 1948 م أنموذجين - عبيد,صباح (University of Eloued جامعة الوادي, 2023)
ملخص: كشفت فرنسا عن بغضها، وأن تصريحاتها مجرد وبال أوهام، في حين اعتدلت نفسية زعماء الحركة الوطنية بمراوغة فرنسا في أساليبها ومحاولة التضليل لإعادة إحياء النضال السياسي من جديد، لافتقار الحياة السياسية للنشاط، فقد تمخض عن الظروف السائدة قوانين سمحت بالنهوض بعد الركود للقادة وفي مقدمتهم فرحات عباس، بسيكولوجية أكثر مرونة في استيعاب طموح الشعب الجزائري لمطلب الهوية الجزائرية وأبلغ شدة في خطاب اللسان الاستعماري ببرنامج أكثر وضوحا والخوض في محطات الانتخابات. ففي الدراسة سنسلط الضوء على المشوار السياسي لفرحات عباس، بتفسير سيكولوجية هذا القائد ودوره في انتخابات المجلس التأسيسي الثاني جوان 1946م و انتخابات المجلس الجزائري أفريل 1948م.Abstract: France has revealed its hatred for its usual approach to the peoples of its colonies, as its statements have shown that its intentions with Algerians to reform are mere delusions, In contrast, it became clear that the psyche of the leaders of the National Movement was accustomed to evading France and its methods and attempting to pretend to allow them to resume the formation of political parties. and participation in the socalled elections at the 1946-1948 stations of an electoral college for Muslims, This motivated party leaders to relaunch the struggle in Algeria, led by Farhat Abbas aspiration to the Algerian identity demand and conveyed the intensity of the colonial rhetoric with a clearer programme and delving into the election stations. In the study, we will highlight Farhat Abbas's political career, explaining the psychology of this leader through his role in the elections for the Second Constituent Assembly of June 1946 and the elections for the Algerian Council of April 1948.
Keywords: فرحات عباس; الجمعية التأسيسية; حزب سياسي; Election; Farhat Abbas; Constituent Assembly; Fraud; a candidate; political party